Efficient Genome Editing in Populus Using CRISPR/Cas12a - An, Yi; Geng, Ya; Yao, Junguang; Fu, Chunxiang; Lu, Mengzhu; Wang, Chun; Du, Juan (Frontiers in Plant Science, 2020)
The ability to create targeted mutations using CRISPR/Cas9 in support of forest tree biotechnology is currently limited. CRISPR/Cas12a is a novel CRISPR effector protein that not only broadens the CRISPR/Cas targeting range but also enables the generation of large fragment deletions. In this study, a CRISPR/Cas12a system was evaluated for the induction of targeted mutations in the woody tree poplar (Populus alba × Populus glandulosa). Three Cas12a nucleases, namely AsCas12a (Acidaminococcus sp. BV3L6), LbCas12a (Lachnospiraceae bacterium ND2006), and FnCas12a (Francisella tularensis subsp. novicidain U112) were used. We knocked out multiple targets of the phytoene desaturase gene 8 (PDS) using the CRISPR/Cas12a genome-targeting system, and the results indicated that the AsCas12a system is the most efficient. We further optimized the cocultivation temperature after Agrobacterium-mediated transformation from 22°C to 28°C to increase the Cas12a nuclease editing efficiency in poplar. AsCas12a showed the highest mutation efficiency, at 70%, and the majority of editing sites were comprised of large-fragment deletions. By using this simple and high-efficiency CRISPR/Cas12a system, multiple targets can be modified to obtain multi-gene simultaneous knockout mutants in tree species, which will provide powerful tools with which to facilitate genetic studies of forest trees.